Nephroprotective effect of losartan in IgA model rat - Xing, Li (J Int Med Res, 2019)
OBJECTIVE: This study was performed to investigate the possible nephroprotective effects of losartan in a rat model of experimental IgA nephropathy (IgAN). METHODS: Thirty male Sprague–Dawley rats were randomly divided into three groups. The rats in the model group were treated with bovine serum albumin (oral gavage), lipopolysaccharide (tail vein injection), and carbon tetrachloride (subcutaneous injection); rats in the losartan group received treatments similar to those of the model group, and were orally gavaged with losartan; and rats in the control group received phosphate-buffered saline alone (both orally and intravenously). RESULTS: Losartan treatment lowered the 24-hour urinary protein, serum blood urea nitrogen, and serum creatinine levels. Proliferating mesangial cells with a variable increase in the mesangial matrix were detected in the model group, whereas injury in the losartan group was significantly attenuated. Immunohistochemistry revealed that the expression levels of transforming growth factor (TGF)-β1 and α-smooth muscle actin were significantly elevated in the model group but reduced in the losartan group. The expression levels of TGF-β1 and monocyte chemoattractant protein-1 were minimal in the control group, significantly increased in the model group, and reduced in the losartan group. CONCLUSION: Losartan has a protective effect against tubulointerstitial injury in IgAN.